Environmental aspects – IoT based cattle movement prevention to avoid road accident for Bhopal-Indore highways in India. (March 2022) - Ashwin, M.; Alqahtani, Abdulrahman Saad; Mubarakali, Azath; Parthasarathy, P.
Abstract: A smart metropolitan area develops Information and Communications Technology (ICT) to renovation of smart transportation features with lower cost and better efficiency. The foremost aim of this study is to pinpoint and resolve the difficulties in Bhopal-Indore highways. The most important smart metropolitan uses are smart protection, smart alive, and smart sustainability. Human and Cattle protection is a main problem in the current urban circumstance. This study will be instigating smart transportation using smart sensor to prevent the cattle movement for Bhopal-Indore highways. Human and Cattle are two sides of the smart transportation. The proposed vibration sensor algorithm (VSA) and camera sensor algorithm (CSA) is used to identify and prevent the cattle movement nearby Bhopal-Indore national highways. The proposed smart transportation features are safe driving, cattle safeguard, human safety, and smart sensor to monitor and prevent cattle movement on national highways, plantation flower smell to prevent cattle movement nearby roadside. The smart city applies smart solutions to smart transportation for Bhopal-Indore highways.